FORMULASI CLAY MASK DAUN BINAHONG (Anredera cordifolia (Ten.) Steenis) DAN UJI INHIBISI Staphylococcus aureus - Asthyananda, Michelytha; Bakri, Dzaki Fikri Firdaus (Fakultas Farmasi Universitas Jenderal Achmad Yani, Indonesia, 2024)
Acne is abnormal skin condition is cause by disruption of oil gland production causees in excessive oil production. One of the bacteria that cause acne is Staphylococcus aureus Binahong leaf (Anredera cordifolia (Ten.) Steenis) has been studied and proven to inhibit Staphylococcus aureus bacteria at 20%. Clay mask is one of pharmaceutical formulations to make it easier for using binahong leaf extract. The purpose of this research is to determine the physical quality test and inhibition activity clay mask with binahong leaf extract against Staphylococcus aureusnbacteria. This study uses the maceration extraction method, formulation of clay mask preparations with a concentration of binahong leaf extract of 10%, 12% and 14%, physical quality tests include organoleptical, homogeneity, pH, viscosity, adhesion, spreadability and drying time of preparations and inhibition Staphylococcus aureus bacteria. The results showed that all clay mask formulas of binahong leaf extract give good physical quality results. The clay mask preparation of binahong leaf extract can inhibition Staphylococcus aureus in formula I is 11,87 ± 0,88, formula II is 13,05 ± 0,44 and formula III is 14,006 ± 1,45. The inhibition activity of the three formulas are classified as strong category.